2009
DOI: 10.1039/b908110k
|View full text |Cite
|
Sign up to set email alerts
|

The giant magnetic anisotropy energy of Fe+ ions in SrCl2

Abstract: We show that values of the magnetic anisotropy energy (MAE), which are about two orders of magnitude larger than the usual ones for transition metal cations in insulators (approximately 0.01-1 cm(-1)), can be found for the less common ion Fe+. In SrCl2:Fe+, the MAE is 93 cm(-1) when calculated using second-order perturbation multi-configurational calculations (CASPT2) while a similar value is found using multi-reference density functional theory (MR-DFT). This result is even larger than other recently reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The opposite happens for the ligands lying at R S from Ni 2+ . This behaviour, consistent with drastic changes in the covalent bonding of the NiO 6 10À complex, has also been observed in the off-centre motion of Fe + impurities in SrCl 2 or KTaO 3 [4,8,9]. We can now compare our results for the Ni 2+ ion embedded in MgO, CaO and SrO with those of other impurity centres like Cr 3+ or Mn 2+ .…”
Section: Results For Impurities In Cubic Oxides: Comparison With Expesupporting
confidence: 86%
See 1 more Smart Citation
“…The opposite happens for the ligands lying at R S from Ni 2+ . This behaviour, consistent with drastic changes in the covalent bonding of the NiO 6 10À complex, has also been observed in the off-centre motion of Fe + impurities in SrCl 2 or KTaO 3 [4,8,9]. We can now compare our results for the Ni 2+ ion embedded in MgO, CaO and SrO with those of other impurity centres like Cr 3+ or Mn 2+ .…”
Section: Results For Impurities In Cubic Oxides: Comparison With Expesupporting
confidence: 86%
“…In cubic insulating lattices, this off-centre motion gives rise to a local symmetry lowering which, in turn, can induce deep changes into the physical and chemical properties associated with the impurity. As an example, the off-centre motion of Fe + impurities in SrCl 2 [3][4][5] or KTaO 3 [6,7] induces a huge magnetic anisotropy associated to the spin of the impurity [8,9]. Aside from this reason, the study of this kind of structural instability in slightly doped materials is also attractive due to its partial relationship [10][11][12] with the ferroelectric distortions in pure insulating materials like BaTiO 3 or PbTiO 3 , where, apart from a local component which could favour the off-centre motion, a cooperative component may also be present.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the particular procedure of controlling the spin and the orbital occupation schemes in DFT simplifies the computation and enables DFT to be the method of choice adapted to this particular problem. We have developed the Ligand Field DFT (LFDFT) approach for the analysis of the spectroscopy and magnetic properties [19][20][21][22][23][24][25][26][27][28][29][30] of an ion centre surrounded by a ligand system, using the early concept of the multideterminental approach. 31 This multideterminental approach is based on the average of configuration (AOC) occupation of the KohnSham orbital, when we are dealing with single-open-shell configurations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that all common molecular properties, for example, zero‐field splitting,10g, 12 Zeeman interactions,13 hyperfine splitting,13 Jahn–Teller (JT) effects,14 magnetic exchange coupling,15 shielding constants,16 electronic structure and transitions in f elements,12a, 17 and f–d transitions,8a, 18 can be calculated by this procedure. LF‐DFT proved to be particularly good for determining the MAEs in trigonal‐bipyramidal Ni 2+ complexes12c and complexes of Fe + 10i. In both cases, LF‐DFT gave excellent agreement with highly accurate MRCI12c and CASPT210i calculations, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…LF‐DFT proved to be particularly good for determining the MAEs in trigonal‐bipyramidal Ni 2+ complexes12c and complexes of Fe + 10i. In both cases, LF‐DFT gave excellent agreement with highly accurate MRCI12c and CASPT210i calculations, respectively. Furthermore, LF‐DFT was able to calculate the very low experimentally observed value of MAE in the acetylacetonate ⋅ Cr 3+ complex, and it was even appropriate for calculations of the MAEs in excited states 19.…”
Section: Introductionmentioning
confidence: 87%